Stress and resilience of nursing students in clinical training during political violence: A palestinian perspective. - Ibrahim Aqtam; Ahmad Ayed; Othman A Alfuqaha; Mustafa Shouli (PLoS ONE, 2025)
Introduction Nursing is one of the most demanding undergraduate degrees because students must master rigorous theory while simultaneously developing hands-on clinical skills. In conflict zones, political violence magnifies these challenges during clinical training. Objective To quantify perceived stress and resilience among Palestinian nursing students during political violence and examine their relationship and demographic associations. Methods In this cross-sectional study, 310 students completed validated Arabic versions of the 29-item Perceived Stress Scale (PSS) and 10-item Connor-Davidson Resilience Scale (CD-RISC-10). Completion time averaged 10-15 minutes total. Analyses included Pearson correlation, t-tests, ANOVA, and multiple regression. Results Mean stress was high (81.1 ± 7.3) based on established PSS cutoffs, while resilience was moderate (28.0 ± 1.8) according to CD-RISC-10 norms. A moderate positive correlation linked stress and resilience (r = 0.314, 95% CI [0.182, 0.442], p < 0.001). Male students reported higher stress than females (t(308) = 2.20, p = 0.030, Cohen's d = 0.25). Conclusion Findings underscore the significant stress burden of political violence on nursing students and signal the need for targeted interventions that address both stress levels and the complex bidirectional relationship with resilience, tailored to demographic risk factors.